2022
DOI: 10.3390/cells11071189
|View full text |Cite
|
Sign up to set email alerts
|

Mitotic Maturation Compensates for Premature Centrosome Splitting and PCM Loss in Human cep135 Knockout Cells

Abstract: Centrosomes represent main microtubule organizing centers (MTOCs) in animal cells. Their duplication in S-phase enables the establishment of two MTOCs in M-phase that define the poles of the spindle and ensure equal distribution of chromosomes and centrosomes to the two daughter cells. While key functions of many centrosomal proteins have been addressed in RNAi experiments and chronic knockdown, knockout experiments with complete loss of function in all cells enable quantitative analysis of cellular phenotypes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…This finding is in accordance with results from the yeast 2-hybrid system, which predicted interaction between Septin 12 and PCM1 (Yeh et al, 2015), a component of centriolar satellites (Dammermann and Merdes, 2002). It has been shown that PCM1 and centriolar satellites play a role in regulating the composition of centrioles (Hall et al, 2023) and conversely, PCM1 requires centrosomal localization of CEP135 for efficient localization around centrosomes (Chu and Gruss, 2022). It suggests that the interaction between Septin 12 and PCM1 may regulate the structure and function of sperm centrioles and that the undetected expression of Septin 12 in the connecting piece of Prm2 -/- sperm could indirectly result in their immotility.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is in accordance with results from the yeast 2-hybrid system, which predicted interaction between Septin 12 and PCM1 (Yeh et al, 2015), a component of centriolar satellites (Dammermann and Merdes, 2002). It has been shown that PCM1 and centriolar satellites play a role in regulating the composition of centrioles (Hall et al, 2023) and conversely, PCM1 requires centrosomal localization of CEP135 for efficient localization around centrosomes (Chu and Gruss, 2022). It suggests that the interaction between Septin 12 and PCM1 may regulate the structure and function of sperm centrioles and that the undetected expression of Septin 12 in the connecting piece of Prm2 -/- sperm could indirectly result in their immotility.…”
Section: Discussionmentioning
confidence: 99%
“…In human cells, C-Nap1 is anchored to centrioles by binding to CEP135. However, CEP135 KO cells still recruit C-Nap1 but with reduced efficiency, indicating alternative docking mechanisms [ 28 ]. Nevertheless, both knockdown [ 29 ] or KO [ 28 ] of CEP135 in cultured mammalian cell lines displayed centrosome linker defects.…”
Section: Molecular Mechanisms Of Centrosome Cohesionmentioning
confidence: 99%
“…However, CEP135 KO cells still recruit C-Nap1 but with reduced efficiency, indicating alternative docking mechanisms [ 28 ]. Nevertheless, both knockdown [ 29 ] or KO [ 28 ] of CEP135 in cultured mammalian cell lines displayed centrosome linker defects. Intriguingly, CEP135 KO in chicken DT40 cells seemed not to result in defects in centrosome cohesion [ 30 ], implying differences in the anchoring of C-Nap1 to centrioles dependent on the organism.…”
Section: Molecular Mechanisms Of Centrosome Cohesionmentioning
confidence: 99%
See 1 more Smart Citation